Purchase Decisions among Non-Muslim: The Role of Islamic Branding, Product Ingredients, and Islamic Social Environment - Erike Anggraeni; Khavid Normasyhuri; Tri Atmaja Pramudita Wisnu Kusuma (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The influence of acculturation on non-Muslims’ purchase decisions remains an unanswered question. Thus, the impact of the Islamic environment on non-Muslim purchase decisions requires further exploration. This study examines how Islamic branding and product ingredients affect purchase decisions and whether the Islamic social environment can strengthen or weaken this relationship for non-Muslim consumers. This study employed a quantitative approach using SmartPLS 3.0. Data were collected from 500 non-Muslim respondents using purposive sampling. The results indicate that both Islamic branding and product ingredients significantly influence non-Muslim purchase decisions, highlighting the growing importance of ethical and cultural considerations in consumer behavior. Moreover, the Islamic social environment plays a crucial role in moderating this relationship, further strengthening the impact of Islamic branding and product ingredients on purchase decisions. These findings suggest that non-Muslim consumers are not only responsive to the intrinsic qualities of products but are also influenced by the broader Islamic social context in which these products are marketed. This offers valuable insights for the government and companies in developing effective strategies to market Indonesian halal meat products to non-Muslim consumers globally. A deeper understanding of non-Muslim purchasing behavior can enhance their position in the halal industry.